The giraffe and the Pelly and me - Dahl, Roald (b, 1992)
A small boy with a desire to own a candy shop meets a window-washing team of a giraffe, a pelican, and a monkey and together they go to work for the wealthy Duke of Hampshire, who makes all their dreams come true.
Keywords: Giraffe -- Juvenile fiction; Monkeys -- Juvenile fiction; Humorous stories